Obsessive-Compulsive Tendencies & Self-Concept Clarity Among Females With and Without Hormonal Imbalance - Zahid Ambreen (Gonabad University of Medical Sciences, 2021)
Background: The role of hormones in the female body is well known in reproductive age. Several studies have been conducted regarding hormonal fluctuations and their association with obsessive-compulsive disorder, but the role of psychological issues relevant to it has been ignored and only hormonal fluctuation and its impact were the target. Thus, the main purpose of this study was to examine the relationship between Self-Concept Clarity (SCC) and obsessive-compulsive tendencies (Obsessive-Compulsive Concerns about Cleanliness (OCC) and Obsessive-Compulsive concerns about Harm and Injury (OCHI)). Another objective was to identify the difference between SCC, OCC, and OCHI in healthy and unhealthy females. Methods: A sample of (N=210) females, an equal number of healthy and unhealthy females, from different hospitals and the general population, with a mean age of 21 years, was selected by using convenience sampling technique as a type of non-probability sampling. Study participants were selected from the same city. Results: Comparison of healthy and unhealthy females revealed high levels of SCC and obsessive-compulsive tendencies among unhealthy females and also a significant positive correlation was found between these constructs. Conclusion: The females with irregular hormonal fluctuations develop obsessive-compulsive tendencies and these people are most sensitive to unimportant affairs, even sensitive to themselves that might create clarity in their self-concept.